Maybelle goes to tea - Speck, Katie (Henry Holt and Co., 2008)
Maybelle the cockroach follows the advice of her new fly friend Maurice and tumbles into a terrifying but tasty adventure during Mrs. Peabody's Ladies' Spring Tea.